REPORTING ON INTELLECTUAL CAPITAL AND ITS IMPACT ON THE VALUE OF THE ECONOMIC UNIT- AN APPLIED STUDY ON PRIVATE IRAQI BANKS (World Economics and Finance Bulletin, 2024)
The research aims to discuss and analyze the theoretical framework for reporting intellectual capital (IC), discuss and analyze the theoretical framework for IC and the requirements for reporting it, and identify the nature and components of IC, methods of measurement, disclosure and the impact of this reporting on the value of private Iraqi banks. The research concluded that intellectual capital includes, in addition to its traditional components, taking into account the dimensions of human resources development for the sake of continuity, identifying the impact of the bank’s structure, the number of committees, and the mechanisms for transferring information between the different administrative levels, which affects the nature and quality of the decisions taken by these levels, and developing relations with... Internal and external parties, and there are several indicators on which the management relies to ensure the sustainability and continuation of these relationships, and that reporting on intellectual capital contributes to raising the value of the bank, and has a clear impact on the nature and quantity of information provided to customers, and this information is what contributes to raising the value of the bank in the market. The research concluded that banks must pay attention to developing and training working cadres in order to keep pace with developments in the markets, and that it is the duty of bank management to attract competent personnel who possess experience in the field of modern electronic programs and systems, and to develop a plan to develop employees by involving them in training courses in their field of specialization to be Keeping pace with developments in the field of specialization, and ensuring flexibility in the organizational structure in order to improve its response to changes in business requirements.
Keywords: Intellectual capital; human capital